Radiation recall pneumonitis in a patient treated by nivolumab for non-small cell lung cancer, no relapse with rechallenge - Thoré, Pierre; Godbert, Benoît; Petit, Isabelle; Chaouat, Ari (European Journal of Oncology and Environmental Health, 2019)
Background: Radiation recall pneumonitis is an inflammatory phenomenon occurring in a previously irradiated area of the lungs in response to precipitating agents. The diagnosis is based on clinical features and radiologic abnormalities in the irradiated field and must occur after the administration of an inciting agent. Report: A 58-years-old woman previously treated by left mastectomy and adjuvant radiotherapy for a breast cancer was diagnosed with a right lung adenocarcinoma. Concomitant radio-chemotherapy with irradiation of the upper part of the right hemithorax was performed. Unfortunately, a new metastasis appeared. A new line of treatment with nivolumab was started. Four weeks after the onset of the checkpoint inhibitor, she presented clinical and imaging criteria evoking the diagnosis of RRP induced by nivolumab. A high dose systemic steroid was introduced. As a result, general state, respiratory conditions and imaging features were improved. Conclusions: Some drugs are known to be associated with RRP, mainly traditional chemotherapies. Patients generally improved their condition after a break of the precipitating agent and with steroids. RRP induced by nivolumab has only been described once in a Japanese case report. It constitutes the first report of such a case in Europe.